2017
DOI: 10.4103/1735-3327.215959
|View full text |Cite
|
Sign up to set email alerts
|

Push-out bond strength of different intracanal posts in the anterior primary teeth according to root canal filling materials

Abstract: Background:This study was carried out to evaluate the effect of root canal filling on the bond strength of three intracanal posts in the primary incisors.Materials and Methods:Sixty primary incisors were prepared and then divided into two groups (n = 30). The first group canals obturated with zinc oxide eugenol (ZOE) and Group 2 canals obturated with Metapex. Further, the two group categories were divided into three subgroups (n = 10): (1) short composite post (SCP), (2) glass fiber posts (GFPs) cemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A prefabricated fiber-reinforced resin composite post is one of the most commonly used posts for restoring severely damaged anterior primary teeth [21]. Previously, fiber posts were used successfully in severely damaged primary teeth in experimental studies [16,20]. A clinical study also showed that fiber post presented an acceptable clinical performance concerning material fracture and retention when restoring severely decayed primary anterior teeth at the 12-month follow-up period [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A prefabricated fiber-reinforced resin composite post is one of the most commonly used posts for restoring severely damaged anterior primary teeth [21]. Previously, fiber posts were used successfully in severely damaged primary teeth in experimental studies [16,20]. A clinical study also showed that fiber post presented an acceptable clinical performance concerning material fracture and retention when restoring severely decayed primary anterior teeth at the 12-month follow-up period [11].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible influential factor on the bond strength of the fiber posts to root canal dentin is the root canal filling materials during endodontic therapy [16]. It has been reported that the root canal filling materials containing eugenol, such as zinc oxide eugenol, can negatively affect the bond strength of the fiber posts cemented with resin cements to the root canal dentin [16]. However, root canal filling materials containing calcium hydroxide, such as Metapex, showed higher post bond strength to the root canal's dentin surfaces than zinc oxide [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations